VectorNet: collaborative mapping of arthropod disease vectors in Europe and surrounding areas since 2010 - Wint, GRW; Balenghien, T; Berriatua, E; Braks, M; Marsboom, C; Medlock, J; Schaffner, F; Van Bortel, W; Alexander, N; Alten, B; Czwienczek, E; Dhollander, S; et al. (European Centre for Disease Prevention and Control, 2023)
Background: Arthropod vectors such as ticks, mosquitoes, sandflies and biting midges are of public and veterinary health significance because of the pathogens they can transmit. Understanding their distributions is a key means of assessing risk. VectorNet maps their distribution in the EU and surrounding areas.